Health behaviors and union dissolution among parents of young children: Differences by marital status. - Jess M Meyer; Christine Percheski (PLoS ONE)
Previous research finds that marriage is associated with better health and lower mortality, and one of the mechanisms underlying this association is health-related selection out of marriage. Using longitudinal survey data from 2,348 couples from the Fragile Families and Child Wellbeing Study, we examine whether certain health behaviors-smoking and binge drinking-are associated with risk of union dissolution among couples with young children. We use discrete time hazard models to test whether associations between health behaviors and union dissolution differ between married and cohabiting parents. We find no statistically significant association between binge drinking and union dissolution for either cohabiting or married couples. Parental smoking, however, is associated with union dissolution. On average, married and cohabiting couples in which both parents smoke have a higher risk of union dissolution than couples in which neither parent smokes. Additionally, father's smoking (in couples in which the mother does not smoke) is associated with union dissolution, but only for married couples. These findings illustrate the importance of considering the health behaviors of both partners and provide further evidence of differences in union dissolution dynamics between married and cohabiting couples.